(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The study assessed the level of adoption and profitability of summer tomato varieties at farm level. Data were collected from 90 randomly selected tomato farmers of Bagherpara, Jashore Sadar and Jhikorgacha upazila of Jashore district. The results indicated that BARI Hybrid Tomato-4 was highly adopted summer tomato variety (75%) followed by BARI Hybrid Tomato-8 (16%) and ACI summer king tomato variety (9%). The adoption level of ploughing, manure and fertilizer use were low, whereas planting time and irrigation were high. Total cost of production of summer tomato was Tk 584822 per hectare whereas Tk 507355 per hectare was variable cost and fixed cost was Tk 77467 per hectare. Among the cost items mancha preparation cost was the highest (26.89 %) and 26.10 % cost was for labor. The average yield of summer tomato was 50.41 t/ha and gross return was 1542300 tk/ha. On the average, benefit cost ratio was found to be 2.64 on full cost basis and 3.04 on cash cost basis. MoP, zipsum and manure were significant effect on summer tomato cultivation. Attack by pest and disease, lack of seed at proper time, lack of agricultural credit and high cost of production were the major constraints for the adoption of summer tomato. Bangladesh J. Agril. Res. 43(4): 575-585, December 2018